Typhus Fever- A Diagnosis Often Missed as A Cause of Fever. - Hasnat, Ferdousi; Mutanabbi, Mahbub; Noman, Farhana; Fatema, Kanij; Jahan, Gulshan Ara; Anne , R Taher (Bangladesh Journal of Child Health, 2024)
Background: In tropical countries epidemic and endemic typhus are sometimes missdiagnosed as typhoid fever. Typhus infection is emerging in the subcontinent and clinically presents as nonspecific febrile illness. So high index of clinical suspicion is essential and the objective of the study was to detect typhus infection as a cause of febrile illness. Materials &Method: This is a prospective observational study done from January to December 2019. A total 50 patients of different age groups were taken randomly who were suffering from fever for more than 7 days. All relevant investigations including CBC, Dengue serological test, Widal test, urine routine examination and C/S, blood C/S, chest x-ray were done. Patients not responding to conventional antibiotic therapy and having persistent fever were further investigated for typhus fever with Weil-Felix test. Results: Out of 50 patients 35 were male; age range was 2 to 12 years. Mean duration of fever was 10 days. Blood for CBC showed nonspecific findings, Blood culture and urine for c/s were negative for bacterial growth, dengue serological tests were negative, chest x-ray were normal (except 2 patients had pneumonia). Weil-Felix tests were positive in all cases. 12 cases were positive for both Widal test and Weil-Felix test and in 8 cases blood c/s were also positive with Weil-Felix test. Treatment changed to Doxycycline or Azithromycin in cases of typhus fever. Conclusion: Typhus fever should be taken into account in the management of febrile illness who were admitted without a confirmed cause of fever. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 54-57